ANALISIS EFISIENSI USAHATANI PADI DI JAWA TENGAH (PENERAPAN ANALISIS FRONTIER) - Darwanto, Darwanto (Jurnal Organisasi dan Manajemen, 2010)
Agriculture development very supposed can to give larger ones contribution in order to increase citizen alive standard. Development opportunity of usahatani padi very depending from efeciency of usahatani. This research tries to see efeciency usahatani padi central java. Research use model frontier to know efeciency. Research result show usahatani padi that run at research region presents in condition increasing returrn to scale (IRS) so that can be said that this condition is proper to be developed. This research also show that usahatani padi inefficient if seen from price efficiency (eh) and economy efficiency (ee).